REFLECTIONS ABOUT HUMAN CARING - Vera Regina Waldow (Universidade Federal do Paraná, 1998)
The article presents some reflections about human caring in nursing nowadays focusing it as an interactive process and not as a technical procedure, only. The author talks about the caring process and the attributes of both, the caring being and the caring for. Finally, makes some considerations about a human caring education which should be "lived" among faculty and students in order to be truly effective in the professional practice.